(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents the creation process of the Cartography of Dance Archive in Acre, a continued action of research and documentation of scenic dance in the state. Based on experiences in the Western Amazon and mapping initiated during the author’s PhD, the study analyzes the impacts of the absence of archives, the recording strategies adopted, and the challenges faced by local artists. The archive is discussed as a device for memory, education, and aesthetic proposition, in dialogue with other initiatives across the country. It is concluded that the productions still point to distant horizons, largely separated from the social and political reality that surrounds and distinguishes them.